2002
DOI: 10.1083/jcb.200203091
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of TRPC in the abnormal calcium influx observed in dystrophic (mdx) mouse skeletal muscle fibers

Abstract: Duchenne muscular dystrophy results from the lack of dystrophin, a cytoskeletal protein associated with the inner surface membrane, in skeletal muscle. The absence of dystrophin induces an abnormal increase of sarcolemmal calcium influx through cationic channels in adult skeletal muscle fibers from dystrophic (mdx) mice. We observed that the activity of these channels was increased after depletion of the stores of calcium with thapsigargin or caffeine. By analogy with the situation observed in nonexcitable cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
306
4
6

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 309 publications
(337 citation statements)
references
References 62 publications
14
306
4
6
Order By: Relevance
“…[36][37][38] This membrane leakage induces abnormal calcium influx followed by activation of the ubiquitous calpains, leading to an excess of unwanted and untimely proteolysis, and finally necrosis of the muscle fiber. [39][40][41] Accordingly, the high numbers of central nuclei found in both models indicate an ongoing cycle of necrosis and regeneration. The two treatments used alleviated the pathophysiological signs, as demonstrated by improved histology and Evans blue dye exclusion.…”
Section: Discussionmentioning
confidence: 86%
“…[36][37][38] This membrane leakage induces abnormal calcium influx followed by activation of the ubiquitous calpains, leading to an excess of unwanted and untimely proteolysis, and finally necrosis of the muscle fiber. [39][40][41] Accordingly, the high numbers of central nuclei found in both models indicate an ongoing cycle of necrosis and regeneration. The two treatments used alleviated the pathophysiological signs, as demonstrated by improved histology and Evans blue dye exclusion.…”
Section: Discussionmentioning
confidence: 86%
“…Endogenous TRPC4 Interacts with Sarcolemmal TRPC1 in Muscle and Cultured Myotubes-The formation in skeletal muscle cells of heterotetrameric channels associating TRPC1 and TRPC4 was explored because the use of antisense had suggested previously that store-operated calcium currents recorded in fibers are dependent on the expression level of TRPC1 and TRPC4 channels (22). Moreover, TRPC1 translocation into the plasma membrane has been shown to depend upon the expression of TRPC4 at the membrane (32).…”
Section: Requirement Of ␣1-syntrophin Ph1a and Pdz Domains (N Terminumentioning
confidence: 99%
“…The activity of MS channels (25)(26)(27) and SOCs (22) is higher in dystrophin-deficient muscle cells. The sarcolemma of dystrophin-deficient muscle also displays cation channels that are active when muscles are at rest, with greater open probability (28), and an antisense strategy suggested that the spontaneously active channels are constituted by TRPC protein (22). These studies and others led to the hypothesis that the DAPC may control TRPC-MS/ SOC channels at the sarcolemma and that is involved in regulating subsarcolemmal calcium concentration.…”
mentioning
confidence: 99%
See 2 more Smart Citations